Fiber-reinforced composite fixed dental prostheses: a 4-year prospective clinical trial evaluating survival, quality, and effects on surrounding periodontal tissues - Wolff, Diana; Wohlrab, Theresa Friederike; Saure, Daniel; Krisam, Johannes; Frese, Cornelia (The journal of prosthetic dentistry, 2018)
Statement of problem Although fiber-reinforced composite fixed dental prostheses (FRC FDPs) are a reliable treatment option for the restoration of single missing teeth, comparatively few prospective clinical trials (PCT) exist. Purpose The purpose of this PCT was to evaluate the survival, quality outcome, and effect of FRC FDPs on periodontal health over 4 years. Material and methods Twenty-six consecutive patients (16 men, 10 women) receiving FRC FDPs with preimpregnated unidirectional fiber reinforcement were included in the trial. Eighteen FRC FDPs were placed in the maxilla and 8 in the mandible. Data from baseline, 12-, 36-, and 48-months of follow-up were recorded, and the prostheses were classified as “success,” “survival,” or “failure.” Periodontal parameters (probing depth, clinical attachment level, plaque index, and bleeding index were assessed, and the quality was rated according to modified United States Public Health Service (USPHS)/Ryge or World Dental Federation (FDI) criteria. Results Functional survival at 4 years was 73.5% (95% confidence interval [CI], 52.9-87.3) with 17 FRC FDPs still functioning. Twelve of these were classified as “success” and 5 as “survival.” Overall survival was 53.0% (95% CI, 30.4-74.4). Six FRC FPDs failed completely. Periodontal parameters did not change over the observation period. Regression analysis showed that probing depth and clinical attachment level did not influence the survival of FRC FDPs. According to USPHS/Ryge/FDI criteria only “wear” and “surface luster” increased significantly over 4 years. Conclusions The survival rate of FRC FPDs confirms existing data. Negative effects on periodontal health were not seen over the period of observation. Aging effects such as wear were recorded and indicated that FRC FPDs are at risk of disintegration, as they are composed of a fiber framework and veneering composite resin.